Re-framing Research in Human-Computer Interaction from the Point-of-View of Activity Theory? - Bødker, Susanne (DAIMI Report Series, 1993)
Within human-computer interaction cognitive science is today the leading approach. Yet its position is threaded philosophically as well as from within the field. Most attempts to re-frame human-computer interaction from within the field are minor revisions to the traditional theoretical basis, still without much to say about real-life computer applications. In this paper I shall present and discuss an alternative approach based on activity theory. The following summarizes the theoretical anchor points: Activity is mediated. That artifacts mediate use means that we are normally not aware of them as such in use, they are transparent to us. Artifacts are seen as historical devices. Although collective, each activity is conducted through actions of individuals. Activities are not taking place in isolation but interwoven with other activities. Artifacts may be the instruments of a web of activities. The concepts of breakdowns and focus shifts are used in the further analysis of specific computer applications in use, and a mapping technique for such analysis is developed. Based on an example I take the first steps towards a more contextualized analysis of human-computer interaction. The human activity framework has provided a vehicle for bringing together an overall analysis of work and use of computer technology with a detailed analysis of human-computer interaction. It provides a way of understanding the relations between the overall socio-political conditions of work and the specific use of the specific computer application in a specific situation. What actually goes on may be analysed from many different levels of activity, where the actual actors are different, and maybe even different from those who conduct the specific actions.